IDENTIFICATION AND QUANTIFICATION OF PINE NEEDLE ESSENTIAL OIL FROM DIFFERENT HABITATS AND SPECIES OF CHINA BY GC-MS AND GC METHOD - Yu, Jingjing; Su, Jie; Li, Fenghua; Gao, Jianli; Li, Bo; Pang, Minxia; Lv, Guiyuan; Chen, Suhong (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Fresh pine needles, which evergreen, renewable and can be collected at any time, have abundant essential oil. The pine needle essential oil possess various biological activities, including antimicrobial, antioxidant, anti-inflammatory, cardioprotective properties etc., and can be widely used as medicine or medical raw materials, fragrances etc. So in order to make full use of pine needle plant resources, especially essential oil, the identification and quantification of essential oil were investigated. Materials and Methods: GC-MS was used to identified compounds in pine needle essential oil of Pinus massoniana Lamb. from Zhejiang, and GC method was developed for determining 5 compounds (namely α-pinene, β-pinene, limonene, bornyl acetate, β-caryophyllene) in pine needle essential oil from different habitats of Pinus massoniana Lamb. and different species (Pinus koraiensis Sieb. et Zucc., Pinus sylvestris var. mongolica Litv., Abies holophylla Maxim.). Hierarchical clustering analysis (HCA) was used to evaluate homogeneity of pine needles in China. Results: 42 compounds(monoterpenes and sesquiterpenes) were identified by GC-MS, which accounted for 99.62% of total essential oil, particularly contained α-and β-pinene (45.23%). Quantification results showed content of bornyl acetate were the lowest, while content of α-pinene, β-pinene were all high except Sichuan, among them α-pinene were higher than β-pinene except for Shandong and Jiangsu, and total content of essential oil in Guangxi is the highest, Jiangsu was the lowest within Pinus massoniana from different habitats. Within pine needle from different species, the highest total content was Pinus koraiensis, the lowest was Pinus sylvestris, Interestingly, the highest content of bornyl acetate was Abies holophylla. By HCA, samples were sorted into two clusters, Abies holophylla and the other, that is Abies holophylla is different from Pinus massoniana, Pinus koraiensis and Pinus sylvestris. Pinus massoniana from Sichuan is different from other Pinus, in which limonene was the highest in all samples. Conclusions: Compounds of pine needle essential oil vary greatly between genus, while smaller between species, so composition differences among pine needle essential oil was related with genus and species. Abies holophylla is different from other pinus species, and Pinus massoniana from Sichuan is different from other habitats. Pine needle essential oil contains abundant α-and β-pinene, which can be used as an alternative raw materials source of pinene. And Abies holophylla and Pinus massoniana from Sichuan can become bornyl acetate and limonene alternative source of raw materials.